2009
DOI: 10.1016/j.coi.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Functional extracellular eosinophil granules: novel implications in eosinophil immunobiology

Abstract: Human eosinophils contain within their cytoplasmic granules multiple preformed proteins, including over three dozen cytokines with nominal Th1, Th2 and immunoregulatory capabilities and four distinctive cationic proteins. The secretion of these granule-derived proteins within eosinophils occurs principally by a mechanism whereby selected proteins are mobilized into vesicles for transport to and release at the cell surface. In contrast, the enigmatic presence of membrane-bound cell free granules extruded from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 42 publications
2
49
0
2
Order By: Relevance
“…Ultrastructural analysis using transmission electron microscopy has distinguished three mechanisms of eosinophil granule release (26). 1) Classic exocytosis involves fusion of granules directly with the cell plasma membrane to release the entirety of the granule contents.…”
mentioning
confidence: 99%
“…Ultrastructural analysis using transmission electron microscopy has distinguished three mechanisms of eosinophil granule release (26). 1) Classic exocytosis involves fusion of granules directly with the cell plasma membrane to release the entirety of the granule contents.…”
mentioning
confidence: 99%
“…However, extensive eosinophil degranulation and pulmonary pathologies could be induced in double-transgenic mice expressing IL-5 and eotaxin-2 coordinately by mature T cells and lung epithelial cells, respectively (47), implying that in vivo eosinophil effector functions mediated by degranulation might involve multiple costimulatory receptor-ligand interactions. In addition, previous studies in man indicated that eosinophil granules are secreted extracellularly as intact membrane-bound structures and that external stimulation is required to elicit secretion from the granules (14,48). The small intestine may lack the endogenous activating signal necessary for the ejection of toxic granular contents from the released MBP + CD63 + granules, preventing any obvious tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Agonists, including Igs (15,16); cytokines, such as IFN-g (17) and ; lipid mediators, such as platelet activating factor (18,19), and the calcium ionophore A23187 (19) were shown to induce the release of eosinophil granule proteins. The stimulus-induced release of eosinophil proteins is a tightly regulated and highly selective process that occurs within minutes of agonist stimulation (14), although its regulatory mechanisms remain to be fully explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their sec re to ry proper ties are un der the con trol of nu me rous membra ne cyto ki ne re cep to rs that enab le se lec ti ve relea se of in di vi dual pro tei ns from extra cel lu lar granu les. Extra cel lu lar gra nu les ha ve been sup po sed to fun ction as en ti re ly in de pen de nt struc tu res and to ad di tio nal ly en han ce lo cal in fl am ma to ry reaction (13,14). Du ri ng the excre tion of the ECP mo lecu le from eo si nop hil gra nu les, en zyma tic deg lycosyla ton oc cu rs that con ver ts the inac ti ve ECP fo rm wi th hi gh mo le cu lar ma ss in to a cyto toxic va ria nt wi th low mo le cu lar ma ss (15).…”
Section: Zrin Ski To Pic R Do Dig S Ecp -Cur Re Nt Con Cep Ts and Cmentioning
confidence: 99%